Pengaruh Kemampuan Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Ketenagakerjaan Dan Transmigrasi Provinsi Bengkulu - Vellya Agustin; Neri Susanti; Eska Prima Monique Damarsiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
To find out the influence of work ability, work motivation, and performance on employee performance in the Employment and Transmigration Office of Bengkulu Province. The sampling technique in this study used the Slovin method That's 67 respondents.Determination test results of 0.678 or 67.8%. This shows that work ability and work motivation affect employee performance in the Employment and Transmigration Office of Bengkulu Province by 67.8%, while the rest (100 - 67.8% = 32.2%). Work ability and work motivation together had a significant influence of 0.000 less than 0.05.